Impulsive buying behavior of millennial TikTok users in the view of Al-Ghazali's maqasid syariah: A study of millennials in West Kalimantan - Holil, Muhammad; Yandi, Pitri (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
The phenomenon of impulse buying on TikTok's Live Shopping feature is increasing among millennials, including in West Kalimantan, in line with the rise of visual-based marketing, flash sales, and real-time interactions. This behavior has the potential to lead to irrational purchasing decisions, so it needs to be studied from the perspective of Al-Ghazali's Maqasid Syariah, particularly in relation to the preservation of wealth (hifz al-mal) and self-control. This study aims to analyze the psychological influence of consumers, social media in purchasing, as well as financial planning and self-control on impulse buying among TikTok Live Shopping users, while assessing its suitability with the principles of Maqasid Syariah. The study uses a mixed method with a quantitative approach through SEM-PLS (SmartPLS 4) and a qualitative approach through in-depth interviews. The sample consisted of 140 millennial respondents in West Kalimantan who actively use TikTok. The outer model evaluation showed that all indicators were valid with a loading factor value ≥ 0.70. The inner model results showed that consumer psychology had a significant effect on impulse buying (β = 0.288; p = 0.001), social media significantly influences purchasing (β = 0.301; p = 0.000), and financial planning and self-control are the most dominant factors (β = 0.386; p = 0.000). Qualitative findings reinforce the statistical results, in which informants admitted to being driven to buy due to visual stimuli, social pressure from comments and shopping notifications, and weak self-control while watching live streams. The results of this study show that impulse buying behavior on TikTok tends to be inconsistent with Al-Ghazali's Maqasid Syariah, especially in terms of protecting property and controlling desires. The novelty of this research lies in the integration of digital consumer behavior analysis through SEM-PLS with a normative evaluation of Maqasid Syariah in the context of TikTok Live Shopping. This research is expected to contribute to the literature on digital Islamic economics and serve as a basis for financial literacy and Islamic consumption education for the millennial generation.